LOS MILAGROS DE SANTIAGO Y LA TRADICIÓN ORAL MEDIEVAL - Ramírez Pascual, Tomás (Antigüedad y Cristianismo, 1995)
Literary exarnples of how the environmental conditions and the moral and social concems influence the formation of traditions. Starting wih a simple pilgrimage miracle, persons and circumstances are added and it finally ends up transforming the moral motivations and teachings which such an event would give.